Establishment of a sheep immortalization cell line for generating and amplifying Orf virus recombinants - Sun, Shihui; Zhao, Kui; Lu, Huijun; Liu, Xingyuan; Li, Yue; Li, Qi; Song, Deguang; Lan, Yungang; He, Wenqi; Gao, Feng; Li, Zi; Guan, Jiyu (Frontiers in Veterinary Science, 2022)
Orf virus (ORFV) causes highly contagious vesiculoulcerative pustular and skin lesions in ruminants like sheep. Developing ORFV-based recombinant vaccine is a potential way to combat Orf disease. Although ORFV could propagate in some kinds of primary cells, the proliferative capacity of primary cells is limited. Therefore, establishing immortalized stable cell line is an effective and affordable way for the production of live ORFV vaccine. In the present study, we introduced a telomerase reverse transcriptase (TERT) gene-expressing cassette into primary ovine fetal turbinate (OFTu) cells, then selected and expanded the cells, which was considered as immortalized OFTu cell line. Our results showed that TERT introduction has successfully expended the lifespan of OFTu cell line over 80 passages, without changing the cellular morphology, affecting chromosomes karyotype and inducing the cellular tumorigenic ability. Immortalized OFTu cell line-derived ORFV has caused similar levels of cytopathic effects (CPE), viral titers and viral particles when compared with the ORFV from primary OFTu cell. Importantly, immortalized OFTu cell line was suitable for generating gene-modified ORFV recombinant through homologous recombination, and for the amplification of ORFV recombinant. In summary, an immortalized OFTu cell line was established and characterized, which could be a powerful tool for preparing ORFV recombinant vaccines.